Ductility analysis of RC beams considering the concrete confinement effect produced by the shear reinforcement: A numerical approach - Nogueira, Caio Gorla [UNESP]; Rodrigues, Isabela Durci [UNESP] (FapUNIFESP (SciELO), 2017)
In this paper, a simplified numerical approach to study the influence of the confinement effect provided by transversal reinforcement on the ductility behavior of RC beams in bending is proposed. A unidimensional FEM mechanical model coupled to the Mazars’ damage model to simulate concrete behavior was adopted to assess ductility curvatures at the ultimate limit state. The confinement effect was incorporated to the numerical model through a calibration process of the damage internal parameters, based on the Least Square Method and an analytical law proposed by Kent and Park (1971). Several numerical analyses were carried out considering different designs of RC beams according to a parametric study varying the neutral axis position, concrete compressive strength and the volumetric transversal reinforcement ratio. The obtained results showed the importance of the amount of transversal reinforcement on the ductility behavior, increasing the ductility factor even for the cases with inappropriate neutral axis position.
Keywords: Concrete; Confinement; Damage; Ductility; Finite element; RC beams